Cognitive Support Technology: Approaches for Postsecondary Students With a Traumatic Brain Injury. (September 2016) - Jacobs, Karen; Nardone, Amanda; Hendricks, Deborah J.; Rumrill, Phillip; Elias, Eileen; Leopold, Anne; Stauffer, Callista; Sampson, Elaine; Scherer, Marcia
Increasingly, traumatic brain injury (TBI) is a serious public health problem affecting ~1.7 million Americans each year. Over 75% of TBIs are classified as mild and these rates are most likely underestimated. Despite the low severity rating, 5-15% of individuals go on to develop chronic, persistent TBI-related symptoms causing functional limitations. Project Career is an interprofessional demonstration providing continued support and services to 2-year and 4-year college students with a history of TBI. This program is designed to improve the employment success through a combination of assistive technology on iPads and individualized career counseling services as undergraduate students transition from university settings to the workplace. This demonstration presentation will engage participants in understanding the Project Career assessments and iPad Apps. Using a case study approach, participants will appraise appropriate Apps and advance their understanding of how the iPad can be used an an educational tool and cognitive support technology (CST).